Detecting activations in unipolar epicardial electrograms recorded during ventricular fibrillation - Blanchard, S.M.; Tohmaz, A.S.; Cervino, D.J.; Pool, T.S.; Clark, B.P.; Johnson, E.E.; Ideker, R.E. (1995 Computers in Cardiology, 1995)
Detecting activations (ACTs) from unipolar electrograms (UEGs) is difficult during ventricular fibrillation (VF) due to the superposition of distant activity from multiple wavefronts. Epicardial UEGs were recorded during the first 2 s of VF from an 11/spl times/11 array of Ag-AgCl electrodes spaced 280 /spl mu/m apart on the LV apex of 5 open-chest pigs. The Rule-Based Method (RBM) used maximum negative derivatives (DERs) located at least 56 ms apart to identify RBM-ACTs while the Transmembrane Current Method (TCM) used electrograms recorded from sites with 4 orthogonal neighbors to estimate I/sub m/ at the center site. Biphasic deflections of I/sub m/ that occurred at the same time as negative DERs were used to indicate TCM-ACTs. All RBM-ACTs with DER /spl les/-1.5 mV/ms (5119 of the 5650 investigated) were assumed to represent true activations. TCM-ACTs confirmed activation for 251 RBM-ACTs with -1.5<DER/spl les/-0.3 mV/ms and suggested electrotonic activity for 139 RBM-ACTs. Activation could not be confirmed or rejected for another 141 RBM-ACTs.